Uso de cuatro niveles de ensilado de pescado en la dieta de cuyes (Cavia porcellus), sobre su rendimiento productivo en la etapa de engorde - Phoco Cruz, Magali Sonia (2019)
The objective of this work was to determine the use of four levels of fish silage in the diet of guinea pigs (Cavia porcellus), on their productive performance in the fattening stage, in the District of La Esperanza, province of Trujillo, Department of La Libertad, for which 48 guinea pigs of the Peruvian line (1/2) weaned at 14 ± 3 days of age, were used, were randomly distributed in 4 treatments with 3 repetitions. The treatments consisted of diets with levels T0 (0%), T1 (10%), T3 (20%) and T4 (30%) of fish silage. The experiment lasted 8 weeks. Weight gain and consumption was higher in T1 (10%), T2 (20%) and T3 (30%) in relation to T0 (0%) (p <0.05) and there was no difference between (T1 (10%), T2 (20%) and T3 (30%)) (p> 0.05). The food conversion was higher in T2 (20%) and T3 (30%). The carcass performance was better in T3 (30%) and the economic compensation was better in T2 (20%). It was concluded that the use of fish silage in the rations improved the productive performance of the guinea pig, being feasible in benefit-cost relation, incorporating up to 20% levels of the ration